The Magician's Elephant - DiCamillo, Kate; Tanaka, Yoko (Somerville, Massachusetts : Candlewick Press, 2023)
When ten-year-old orphan Peter Augustus Duchene encounters a fortune teller in the marketplace one day and she tells him that his sister, who is presumed dead, is in fact alive, he embarks on a remarkable series of adventures as he desperately tries to find her.
Keywords: Orphans -- Juvenile fiction; Missing children -- Juvenile fiction; Elephants -- Juvenile fiction; Adventure stories; Siblings -- Juvenile fiction; Fantasy fiction; Orphans -- Fiction; Missing children -- Fiction; Elephants -- Fiction; Siblings -- Fiction; Fantasy; Children's stories; Juvenile Fiction